MULTILEVEL SPINAL EPIDURAL EMPYEMA: SERIES OF CLINICAL CASES AND BIBLIOGRAPHIC - Juan Manuel Velasco-canziani; Sergio Conti; Nicolas Galli; Leonardo Pereyra; Natalia Otero; Fernando Garcia; Alvaro Rocchietti; Santiago Sapriza (Coluna/Columna, 2024)
ABSTRACT Multilevel spinal epidural empyema (SEE) is a rare and serious infection of the spine with a high rate of morbidity and mortality. Although abscesses or empyema of the spine sector are well studied, this pathology is surprising due to its rarity and diagnostic and therapeutic challenge. It stands out for being more common in adulthood and in males and is associated with predisposing pathologies. The bacteriological agent responsible in most cases is Staphylococcus aureus. Early treatment is essential and is based on two pillars: antibiotic therapy and decompressive surgery. We present two clinical cases with multilevel involvement that evolved favorably both infectiously and neurologically without causing spine instability and we carried out a bibliographic review of the subject. Level of Evidence IV; Case Report.